In Situ Nanoscale Dynamics Imaging in a Proton‐Conducting Solid Oxide for Protonic Ceramic Fuel Cells. Issue 25 (24th June 2022) - Gorobtsov, Oleg; Song, Yumeng; Fritz, Kevin; Weinstock, Daniel; Sun, Yifei; Sheyfer, Dina; Cha, Wonsuk; Suntivich, Jin; Singer, Andrej
Abstract: Hydrogen fuel cells and electrolyzers operating below 600 °C, ideally below 400 °C, are essential components in the clean energy transition. Yttrium‐doped barium zirconate BaZr0.8 Y0.2 O3‐d (BZY) has attracted a lot of attention as a proton‐conducting solid oxide for electrochemical devices due to its high chemical stability and proton conductivity in the desired temperature range. Grain interfaces and topological defects modulate bulk proton conductivity and hydration, especially at low temperatures. Therefore, understanding the nanoscale crystal structure dynamics in situ is crucial to achieving high proton transport, material stability, and extending the operating range of proton‐conducting solid oxides. Here, Bragg coherent X‐ray diffractive imaging is applied to investigate in situ and in 3D nanoscale dynamics in BZY during hydration over 40 h at 200 °C, in the low‐temperature range. An unexpected activity of topological defects and subsequent cracking is found on a nanoscale covered by the macroscale stability. The rearrangements in structure correlate with emergent regions of different lattice constants, suggesting heterogeneous hydration. The results highlight the extent and impact of nanoscale processes in proton‐conducting solid oxides, informing future development of low‐temperature protonic ceramic electrochemical cells. Abstract : Proton‐conducting ceramics open new horizons for hydrogen energy devices in the lower operating temperature ranges, promising higher energy efficiency. Nevertheless, nanostructure plays a more important role in lowering the operating temperature. Presented here are the results of in situ X‐ray imaging of nanostructure dynamics in BaZr0.8 Y0.2 O3‐d during hydration, exposing a unique degree of freedom in proton‐conducting solid oxide materials.